Etiology of bacteremia and antibiogram of bacterial isolates in padiatric patients attending tertiary care hospital, Kathmandu, Nepal. - Dahal,Sujata (2019)
ABSTRACT: Blood stream infection is common problem in both developed and developing countries. Bacteria may enter the bloodstream through any route, giving rise to bacteremia. It is important cause of serious morbidity and leading cause of mortality. This study was conducted with an objective to determine the etiological agents of bacteremia and antibiogram of bacterial isolates among pediatric patients. This study was carried out at the Microbiology Laboratory of International Friendship Children's Hospital, Kathmandu, Nepal from October 2018 to April 2019. A total of 732 blood specimen were collected and processed accordingly. Antibiotic susceptibility testing was done using Kirby Bauer disc diffusion technique and antibiotics were selected using CLSI (Clinical and Laboratory Standard Institute 2014). Out of 732 blood specimens received from patients suspected of bacteremia, 134(18.31%) showed bacterial growth. Gram positive isolates were 47.8% and Gram negative isolates were 52.2%. Staphylococcus aureus 41(30.6%) was the most common isolate among Gram positive bacteria followed by coagulase negative Staphylococci 23(17.2%). Acinetobacter spp. 19(14.2%) was the most common isolate among Gram negative isolates. Meropenem, chloramphenicol, gentamicin was found most effective antibiotic against Gram positive bacteria and meropenem, cotrimoxazole, chloramphenicol was found most appropriate drug against Gram negative bacteria. Out of 134 positive blood culture specimens, 71(52.9%) were MDR, whereas 8 of them are ESBL producers, 6 of them were MBL producers and none of them were AmpC producers. 3 of them were NARS strains. MRSA and MLSB were detected in 19(46.34%) and 6(14.64%) of Staphylococcus aureus isolates respectively. In conclusion Gram negative bacteremia is common in children and drug resistance is a major problem in childhood blood borne infections. The isolation of etiological agents of blood stream infection should be assessed by proper microbiological analysis and it would be helpful for controlling of the outbreaks of resistance strains through effective empirical therapy. Key Words: Bacteremia, Pediatrics, Multi drug resistance, ESBL